400 metre race pace strategies: How your 200 metre personal best influences your performance options - Willis, R.; Burkett, B.; Sayers, M. (Journal of Fitness Research, 2012)
Running the ideal 400 m race strategy is the goal for many athletes, unfortunately the demands of the event often hinder their training performance. The choice of initial race speed has a significant effect on the ability to preserve time during the 3rd 100 m split, which had a very strong correlation with final time (r=.90, .89, p<.01) for females and males respectively. Identifying a particular percentage of an athlete's 200 m personal best has been proposed as a modifier of late race deceleration. Central regulatory control has been implicated as the primary influence in maintaining functional homeostasis during intense exercise. It appears to be regulated by the rate of perceived exertion (RPE) which in turn has been linked to an athlete's current maximum speed and the percentage of this speed used to maintain race pace. Increasing maximum speed and lowering an athlete`s current 200 m personal best are seen to be the key contributors to continued improvement in 400 m performance.